The Development a Digital Citizenship Scale for Junior High School Students - ศรีนวล, ศศิวิมล; Saopao, Kantiya; Ongardwanich, Namthip (Research and Development Journal Sisaket Rajabhat University, 2021)
Developing a digital citizenship scale for junior high school students. The aim is to create and determine the quality of a digital citizenship scale for junior high school students. The sample group consisted of 108 lower secondary school students. The research instrument was the Digital Citizenship Scale for Lower Secondary Students. Divided into two parts. Part one is general information of the respondents. The second part is a digital citizenship scale. There were 34 questions. It is a 5-level estimator (most practice (5) - least practical (1)), consisting of 3 components: 1) Respect for yourself and others in the digital world. 2) Be responsible by using digital. 3) Create digital innovation. Data were analyzed by estimating the internally consistent sentiment. The results revealed that the digital citizenship scale for high school students There was a high confidence value of 0.921 and the structural validity of the digital citizenship scale was examined. By second corroborative component analysis, the model was consistent with the empirical data (Chi-square = 28.452, df = 22, P = 0.1612, RMSEA = 0.052, CFI = 0.993, TLI = 0.989, SRMR = 0.026.)